Question
upstudy study bank question image url

For \( f(x)=\frac{6}{x-5} \) and \( g(x)=\frac{7}{x} \), find the following composite functions and state the domain of each. \( \begin{array}{llll}\text { (a) } f \circ g & \text { (b) } g \circ f & \text { (c) } f \circ f & \text { (d) } g \circ g\end{array} \) \( \begin{array}{l}\text { (a) }(f \circ g)(x)=\square \\ \text { (Simplify your answer. Use integers or fractions for any numbers in the expression.) }\end{array} \)

Ask by Cole Bates. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

(a) \( (f \circ g)(x) = \frac{6x}{7 - 5x} \) with domain \( x \neq 0, \frac{7}{5} \) (b) \( (g \circ f)(x) = \frac{7x - 35}{6} \) with domain \( x \neq 5 \) (c) \( (f \circ f)(x) = \frac{6(x - 5)}{31 - 5x} \) with domain \( x \neq 5, 6 \) (d) \( (g \circ g)(x) = x \) with domain \( x \neq 0 \)

Solution

To find the composite functions \( f \circ g \), \( g \circ f \), \( f \circ f \), and \( g \circ g \), we will follow these steps: 1. **Calculate each composite function.** 2. **Determine the domain of each composite function.** ### (a) \( (f \circ g)(x) \) The composite function \( (f \circ g)(x) \) is defined as \( f(g(x)) \). 1. Substitute \( g(x) \) into \( f(x) \): \[ g(x) = \frac{7}{x} \] Therefore, \[ f(g(x)) = f\left(\frac{7}{x}\right) = \frac{6}{\frac{7}{x} - 5} \] 2. Simplify the expression: \[ f\left(\frac{7}{x}\right) = \frac{6}{\frac{7 - 5x}{x}} = \frac{6x}{7 - 5x} \] Thus, \[ (f \circ g)(x) = \frac{6x}{7 - 5x} \] ### Domain of \( f \circ g \) The domain of \( f \circ g \) is determined by the restrictions from both \( g(x) \) and \( f(x) \): - \( g(x) \) is undefined when \( x = 0 \). - \( f(g(x)) \) is undefined when \( g(x) = \frac{7}{x} = 5 \), which gives \( x = \frac{7}{5} \). Thus, the domain of \( f \circ g \) is: \[ \text{Domain: } x \in \mathbb{R} \setminus \{0, \frac{7}{5}\} \] ### (b) \( (g \circ f)(x) \) The composite function \( (g \circ f)(x) \) is defined as \( g(f(x)) \). 1. Substitute \( f(x) \) into \( g(x) \): \[ f(x) = \frac{6}{x - 5} \] Therefore, \[ g(f(x)) = g\left(\frac{6}{x - 5}\right) = \frac{7}{\frac{6}{x - 5}} = \frac{7(x - 5)}{6} \] Thus, \[ (g \circ f)(x) = \frac{7(x - 5)}{6} = \frac{7x - 35}{6} \] ### Domain of \( g \circ f \) The domain of \( g \circ f \) is determined by the restrictions from both \( f(x) \) and \( g(x) \): - \( f(x) \) is undefined when \( x = 5 \). - \( g(f(x)) \) is defined for all \( f(x) \) except when \( f(x) = 0 \), which does not occur since \( f(x) \) is never zero. Thus, the domain of \( g \circ f \) is: \[ \text{Domain: } x \in \mathbb{R} \setminus \{5\} \] ### (c) \( (f \circ f)(x) \) The composite function \( (f \circ f)(x) \) is defined as \( f(f(x)) \). 1. Substitute \( f(x) \) into itself: \[ f(f(x)) = f\left(\frac{6}{x - 5}\right) = \frac{6}{\frac{6}{x - 5} - 5} \] 2. Simplify the expression: \[ f\left(\frac{6}{x - 5}\right) = \frac{6}{\frac{6 - 5(x - 5)}{x - 5}} = \frac{6(x - 5)}{6 - 5x + 25} = \frac{6(x - 5)}{31 - 5x} \] Thus, \[ (f \circ f)(x) = \frac{6(x - 5)}{31 - 5x} \] ### Domain of \( f \circ f \) The domain of \( f \circ f \) is determined by the restrictions from \( f(x) \): - \( f(x) \) is undefined when \( x = 5 \). - \( f(f(x)) \) is undefined when \( f(x) = 5 \), which gives \( x = 6 \). Thus, the domain of \( f \circ f \) is: \[ \text{Domain: } x \in \mathbb{R} \setminus \{5, 6\} \] ### (d) \( (g \circ g)(x) \) The composite function \( (g \circ g)(x) \) is defined as \( g(g(x)) \). 1. Substitute \( g(x) \) into itself: \[ g(g(x)) = g\left(\frac{7}{x}\right) = \frac{7}{\frac{7}{x}} = x \] Thus, \[ (g \circ g)(x) = x \] ### Domain of \( g \circ g \) The domain of \( g \circ g \) is determined by the restrictions from \( g(x) \): - \( g(x) \) is undefined when \( x = 0 \). Thus, the domain of \( g \circ g \) is: \[ \text{Domain: } x \in \mathbb{R} \setminus \{0\} \] ### Summary of Results - \( (f \circ g)(x) = \frac{6x}{7 - 5x} \) with domain \( x \in \mathbb{R} \setminus \{0, \frac{7}{5}\} \) - \( (g \circ f)(x) = \frac{7x - 35}{6} \) with domain \( x \in \mathbb{R} \setminus \{5\} \) - \( (f \circ f)(x) = \frac{6(x - 5)}{31 - 5x} \) with domain \( x \in \mathbb{R} \setminus \{5, 6\} \) - \( (g \circ g)(x) = x \) with domain \( x \in \mathbb{R} \setminus \{0\} \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To find the composite functions, let's evaluate each one step by step. ### (a) \( (f \circ g)(x) \) To find \( (f \circ g)(x) \), we need to substitute \( g(x) \) into \( f \): \[ g(x) = \frac{7}{x} \quad \implies \quad f(g(x)) = f\left(\frac{7}{x}\right) = \frac{6}{\frac{7}{x} - 5} \] Let's simplify: \[ = \frac{6x}{7 - 5x} \] **Domain:** We need \( x \neq 0 \) (from \( g(x) \)) and \( 7 - 5x \neq 0 \) leading to \( x \neq \frac{7}{5} \). Thus, the domain is \( x \in \mathbb{R}, x \neq 0, \frac{7}{5} \). ### (b) \( (g \circ f)(x) \) To find \( (g \circ f)(x) \), we substitute \( f(x) \) into \( g \): \[ f(x) = \frac{6}{x - 5} \quad \implies \quad g(f(x)) = g\left(\frac{6}{x - 5}\right) = \frac{7}{\frac{6}{x - 5}} \] Simplifying this gives: \[ = \frac{7(x - 5)}{6} = \frac{7x - 35}{6} \] **Domain:** We need \( x - 5 \neq 0 \) (so \( x \neq 5 \)) and since \( f(x) \) is defined for \( x \neq 5 \), the domain is \( x \in \mathbb{R}, x \neq 5 \). ### (c) \( (f \circ f)(x) \) To find \( (f \circ f)(x) \): \[ f(f(x)) = f\left(\frac{6}{x - 5}\right) = \frac{6}{\frac{6}{x - 5} - 5} \] Simplifying: \[ = \frac{6(x - 5)}{6 - 5(x - 5)} = \frac{6(x - 5)}{35 - 5x} \] **Domain:** We require \( x \neq 5 \) and \( 35 - 5x \neq 0 \) (leading to \( x \neq 7 \)). Thus, the domain is \( x \in \mathbb{R}, x \neq 5, 7 \). ### (d) \( (g \circ g)(x) \) To find \( (g \circ g)(x) \): \[ g(g(x)) = g\left(\frac{7}{x}\right) = \frac{7}{\frac{7}{x}} = x \] **Domain:** Since \( g(x) \) is undefined at \( x = 0 \), the domain is \( x \in \mathbb{R}, x \neq 0 \). In summary: - \( (f \circ g)(x) = \frac{6x}{7 - 5x} \) with domain \( x \in \mathbb{R}, x \neq 0, \frac{7}{5} \) - \( (g \circ f)(x) = \frac{7x - 35}{6} \) with domain \( x \in \mathbb{R}, x \neq 5 \) - \( (f \circ f)(x) = \frac{6(x - 5)}{35 - 5x} \) with domain \( x \in \mathbb{R}, x \neq 5, 7 \) - \( (g \circ g)(x) = x \) with domain \( x \in \mathbb{R}, x \neq 0 \)

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy